2006
DOI: 10.1515/znc-2006-9-1021
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Monitoring of the Light-Induced Cyclic Photosynthetic Electron Flow during Cold Hardening in Wheat Leaves

Abstract: The effect of irradiance during low temperature hardening was studied in a winter wheat variety. Ten-day-old winter wheat plants were cold-hardened at 5 ∞C for 11 days under light (250 μmol m Ð2 s Ð1 ) or dark (20 μmol m Ð2 s Ð1 ) conditions. The effectiveness of hardening was significantly lower in the dark, in spite of a slight decrease in the F v /F m chlorophyll fluorescence induction parameter, indicating the occurrence of photoinhibition during the hardening period in the light. Hardening in the light ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…2 A and C). This band shift is indicative of an activation of the cyclic electron pathway: electrons are rapidly transferred to the secondary quinone acceptor (Q B ) at room temperature, leading to charge recombination between Q B − and the S states and to the merging of the afterglow band with the B band (28,29). This activation was not observed in ndh1 mutant leaves.…”
Section: Resultsmentioning
confidence: 97%
“…2 A and C). This band shift is indicative of an activation of the cyclic electron pathway: electrons are rapidly transferred to the secondary quinone acceptor (Q B ) at room temperature, leading to charge recombination between Q B − and the S states and to the merging of the afterglow band with the B band (28,29). This activation was not observed in ndh1 mutant leaves.…”
Section: Resultsmentioning
confidence: 97%
“…This result is in accordance with our previous reports that, using dark reduction of the oxidized primary electron donor in PS1 (P700 + ), salt stress stimulated the increase of CEF1 much more in G. cyrtoloba than in G. max (Yang et al 2007) and G. cyrtoloba could maintain higher non-photochemical quenching due to state transition under salt treatment (Yang et al 2006). Though the function of CEF1 on temperature tolerance has been proved in some other higher plant species including cotton , barley and maize (Egorova et al 2002); tobacco (Wang et al 2006), wheat (Apostol et al 2006), the function of CEF1 on salt tolerance has only been reported by Liu and Shen (2006) with halotolerant green alga Dunaliella salina. Our results showed that CEF1 might play an important role in tolerance of soybean G. cyrtoloba to salt stress.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that low temperature hardening in normal light is significantly more efficient than hardening under low light conditions in winter rye (Gray et al, 1997) and winter wheat plants (Apostol et al, 2006;Janda et al, 2007). Growing winter wheat or rye plants at non-hardening temperature but under elevated light conditions may also increase the survival rate (Gray et al, 1997;Janda et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In winter rye and wheat plants, it has been shown that frost hardening at low temperature under low light conditions is much less effective than under normal light conditions (Gray et al, 1997;Apostol et al, 2006;Janda et al, 2007). A certain level of freezing tolerance could also be induced by high light treatment even at normal non-hardening temperature.…”
Section: Introductionmentioning
confidence: 99%